2019
DOI: 10.1590/s2175-97902019000118157
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic activity evaluation of Onobrychis species on alloxan-induced diabetic mice

Abstract: In the current study, four Onobrychis species, O. albiflora Hub.-Mor., O. argyrea Boiss. subsp. argyrea Boiss., O. galegifolia Boiss., and O. tournefortii (Willd.) Desv. were collected from Anatolia to be evaluated for their antidiabetic activities. Methanol water extracts of the aerial parts were used for experiments. An alloxan-induced diabetic mice test model was used. Phytochemical analysis of the tested extracts was investigated using the HPLC method. The highest activity was observed with treatment of O.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…A substance known to cause diabetes, alloxan enters the beta cells of the islets of Langerhans via the GLUT2 transporter, where it inhibits glucokinase and produces reactive oxygen species (ROS) [ 47 , 48 ]. Mice that receive alloxan intraperitoneally at a dose of 150 mg/kg may experience chronic hyperglycemia [ 39 , 48 ]. Similar results were found in our investigation, where the diabetic control group's BGL did not alter significantly during the two-week study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substance known to cause diabetes, alloxan enters the beta cells of the islets of Langerhans via the GLUT2 transporter, where it inhibits glucokinase and produces reactive oxygen species (ROS) [ 47 , 48 ]. Mice that receive alloxan intraperitoneally at a dose of 150 mg/kg may experience chronic hyperglycemia [ 39 , 48 ]. Similar results were found in our investigation, where the diabetic control group's BGL did not alter significantly during the two-week study.…”
Section: Discussionmentioning
confidence: 99%
“…Before receiving alloxan, the animals went on a 16-hour fast [35]. Fresh solutions of alloxan were given intraperitoneally to each mouse at a dose of 150 mg/kg after being dissolved with the appropriate volume of normal saline (0.9%) [38][39][40]. Following the administration of alloxan, animals were examined for diabetes 72 hours later, and those with fasting BGL higher than 200 mg/dl were designated as diabetic mice for the study [35,39,41,42].…”
Section: Oral Glucose Tolerance Test (Ogtt) In Mice Withmentioning
confidence: 99%
“…Before alloxan administration, the mice have been subjected to sixteen hours of fasting. Fresh alloxan solution was prepared using normal saline (0.9%) and administered intraperitoneally at the dose of 150 mg/kg according to previous studies [ 26 28 ]. The mice were screened for glucose levels after 72 hours of alloxan administration.…”
Section: Methodsmentioning
confidence: 99%
“…The mice were screened for glucose levels after 72 hours of alloxan administration. Animals with fasting blood glucose levels >200 mg/dl were included in the study as diabetic mice [ 28 30 ]. After the screening, diabetic mice were randomly allocated to the different test groups.…”
Section: Methodsmentioning
confidence: 99%
“…Özbek et al. (2019) suggested that methanol water extracts of the aerial parts antidiabetic activities of Onobrychis albiflora Hub‐Mor., Onobrychis argyrea Boiss. subsp.…”
Section: Potential Uses Of Wild Onobrychis Speciesmentioning
confidence: 99%